Migraine - Kozubski, Wojciech (IntechOpen, 2020)
The book, Migraine, covers - to our best belief - the most important topics in migraine study, such as spontaneous primary headache, mostly from a clinical and therapeutic point of view. Special attention was paid to two hot topics in migraine problems: the chronic type of migraine and the new contemporary mode of treatment (for both episodic and chronic types) that is the use of monoclonal antibodies directed against the CGRP complex. The separate chapters cover the problem of medication overuse headaches, which is a growing condition among patients with migraine - especially the chronic migraine. The unique problem touched by the book is rarely discussed in literature of this field and it is the surgical attempts in the therapy of migraine. The authors of the book are widely recognized experts in migraines and related headaches that - we do believe - ensures a high quality of knowledge in the book. We hope that the presented monograph will be both attractive and helpful to all doctors interested not only in migraines but in other problems of idiopathic headaches.